Development of Interactive Storybook Media to Enhance Language Skills of Children Aged 4–5 Years - Megawati; Azizah Azizah; Syamsuardi Syamsuardi; Herlina Herlina; Muhammad Akil Musi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The development of early childhood language skills requires learning media that are engaging, developmentally appropriate, and capable of actively involving children in meaningful learning experiences. However, classroom practices often rely on limited and less interactive media, which may hinder optimal language development. This study aimed to develop an interactive storybook learning media and examine its validity, practicality, and effectiveness in enhancing early childhood language abilities, including receptive language, expressive language, and early literacy skills. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of define, design, develop, and disseminate stages. The research was conducted at Runiah School Kindergarten in Makassar, involving teachers and children in a limited field trial. Data were collected through observation, documentation, expert validation sheets, teacher response questionnaires, and children’s language development assessments, and were analyzed using descriptive qualitative analysis and quantitative techniques, including the Wilcoxon Signed-Rank Test. The results indicate that the interactive storybook media achieved a very high level of validity based on expert evaluation, was categorized as very practical according to teacher responses, and proved effective in significantly improving children’s language abilities, with most children reaching the Developing as Expected category and no longer classified as Not Yet Developed. The findings reveal that interactive storybook media not only enhance language outcomes but also increase children’s engagement, interest in reading, and active participation during learning activities. These results imply that interactive storybook media can serve as an effective and innovative alternative learning resource for early childhood educators, supporting language development while aligning with technological advancements and child-centered learning principles.